The effect of varying the detergent concentration and the applied voltage on foam height - Apolega, Mark Raymund G. (Animo Repository, 1997)
The study focused on two parameters in the study of foam lift technology. The two factors under study were concentration of the detergent solution and the voltage applied at the electrode, and how these affected the height of the foam generated in the column. The aim of the study was to determine if these parameters were significant and if these parameters were interacting in generating the foam. Statistical methods were used to achieve the objective. The result of the study showed that the significant factor was the detergent concentration and the voltage applied has no significant effect on the height of the foam. The results likewise showed that there is no interaction between these parameters.